Solar cycle effect on oscillations in the period range of 2-20 days in the F region of the ionosphere - P. Mlch; J. Lastovicka (Annals of Geophysics, 1996)
The results of Lastovicka and Mlch (1994) and Altadill and Lastovicka (1996) are extended by the use of f0F2 and h'F data from Juliusruh, Lannion and Rome. There is a strong solar cycle effect in amplitudes of oscillations in f0F2 but none or a weak solar cycle effect in relative amplitudes of oscillations in f0F2 and in amplitudes of oscillations in h'F. The conditions when the planetary wave type oscillations should be taken into account in short-term predictions and when, on the other hand, they need not be taken into account, are partly specified.